Sistem Kontrol Stop Kran Otomatis Berdasarkan Deteksi Kebocoran Pipa Air Rumah Tangga Berbasis Arduino - Jefrina Dian Stifvani; Yudi Kristyawan; Edi Prihartono (Router : Jurnal Teknik Informatika dan Terapan, 2025)
Water is an essential resource for every household. Typically, household water distribution systems rely on PVC pipes and faucets. Despite this, water leakage remains a frequent issue, occurring in both pipes and taps. This study aims to design an Arduino-based automatic faucet control system capable of detecting leaks in water pipes, with the goal of conserving water and improving usage efficiency. The system employs a pressure sensor to monitor water pressure within the pipe, an ultrasonic sensor to detect user presence at the tap, and a solenoid valve to automatically shut off the water supply in the event of a leak. Testing and design outcomes indicate that the system functions effectively. The solenoid valve successfully closes the water flow automatically when a leak is detected. However, the current system lacks a notification feature to alert users when a leak occurs. Future developments should consider integrating a notification mechanism to inform users promptly about any detected leaks.